Providing Innovation Opportunities Can Increase Employee Satisfaction and Performance on Small and Medium Shoes Industry - Hasani, Syaiful; Sudarmiatin, Sudarmiatin; Pradana, Ludi Wishnu (Eastasouth Institute, 2023)
To be able to survive the global economic, every business organization is forced to continue to innovate and small and medium industry (SMEs) are deemed capable of winning the competition in the industry. SMEs have the freedom to move and innovate because they are still small in scope, so innovation are needed in order to have a competitive advantage. This study investigates the direct and indirect effects of strategic innovation on employee performance by analysing its influence on work satisfaction. The research sample consists of 120 employees from the small and medium shoe business in East Java. The cluster random sampling approach was used to choose the participants. The data analysis model employs the PLS (Partial Least Squares regression) analysis approach with the Smart PLS version 3.0 software. The findings of hypothesis testing indicate that there is no significant direct impact of strategic innovation on employee performance. Employee performance is directly influenced by job happiness. However, strategic innovation has an indirect impact on employee performance by influencing work happiness. This suggests that work happiness might establish a link between the impact of strategic innovation and employee performance.